Toxoplasma metabolic flexibility in different growth conditions. Issue 9 (September 2022) - Walsh, Daniel; Katris, Nicholas J.; Sheiner, Lilach; Botté, Cyrille Y.
Abstract : Apicomplexan parasites have complex metabolic networks that coordinate acquisition of metabolites by de novo synthesis and by scavenging from the host. Toxoplasma gondii has a wide host range and may rely on the flexibility of this metabolic network. Currently, the literature categorizes genes as essential or dispensable according to their dispensability for parasite survival under nutrient-replete in vitro conditions. However, recent studies revealed correlations between medium composition and gene essentiality. Therefore, nutrient availability in the host environment likely determines the requirement of metabolic pathways, which may redefine priorities for drug target identification in a clinical setting. Here we review the recent work characterizing some of the major Toxoplasma metabolic pathways and their functional adaptation to host nutrient content. Highlights: Apicoplast fatty-acid synthase complex (FASII) genes in apicomplexan parasites are essential but only under low host lipid content. Toxoplasma infection is affected by the availability of host nutrients, which determines the essentiality of parasite metabolic pathways. Some parasite metabolic genes are essential only under starvation, which redefines the requirements of essentiality of a metabolic pathway as specific to the physiological states and fluctuations of the host environment.